Respecting life: a human obligation - review - Westra, Laura, author; American Institute of Biological Sciences, publisher (Colorado State University. Libraries, 2013)
The richness of the field of environmental ethics is, for the most part, fully showcased in Holmes Rolston III's new book. Among the strengths of the book is Rolston's outstanding, in-depth treatment of organisms, species, natural systems, wilderness, and nature's intrinsic value. Equally outstanding is his encyclopedia, although at times selective, knowledge of the field of environmental ethics. The main shortcoming is Rolston's limited treatment of environmental justice.
Review of Holmes Rolston, III, A new environmental ethics: the next millennium for life on Earth
Keywords: intrinsic value; environmental ethics; Rolston, Holmes, 1932-2025; biodiversity; environmental justice